Предмет: Алгебра,
автор: megatel3393
Представьте выражение в виде многочлена
1) (0,2х-5у)³
2) (3а-0,6b)³
Ответы
Автор ответа:
6
(0,2х-5у)³= (0,2x)^3-3(0,2x)^2*2(5y)+3(0,2x)(5y)^2-(5y)^2=0.008x^3-1,2x^2y+15xy^2-25y^2
(3а-0,6b)³=(3a)^3-3(3a)^2*2(0,6b)^2+3*3a(0,6b)^2-(0,6b)^2=27a^3-32,4a^2b+5,4ab^2-0,36b^2
Похожие вопросы
Предмет: Українська мова,
автор: strqxz
Предмет: Геометрия,
автор: tkacuklena564
Предмет: Русский язык,
автор: nuriksakhiev007
Предмет: Алгебра,
автор: саша3268
Предмет: Музыка,
автор: pchest